Sosialisasi Ice Breaking Dalam Peningkatan Kompetensi Profesional Guru SMA Negeri 6 Padangsidimpuan - Eni Sumanti Nasution; Tinur Rahmawati Harahap; Fauziah Nasution; Dewita Rosanti Siregar (Yayasan Perguruan Kampus, 2023)
State High School 6 is located in Padangsidimpuan, precisely on Jalan Sutan Soripada Mulia. In this activity, after observing, it was discovered that the ice breaking activity was something new and had never been implemented in schools. In learning, many teachers still use teacher-centered learning, resulting in interesting learning. This activity aims to find out how to apply ice breaking in improving teacher professionalism. The sample used was teachers at Padangsidimpuan State High School 6. The method implemented is through preparation, namely by conducting observations in the field, carrying out a presentation to the teacher about the ice breaking, evaluating and analyzing the teacher's perception of the activity. The results obtained show that teachers really rate this activity positively because it can increase teachers' knowledge in the teaching and learning process so that learning does not make students bored and can increase teacher professionalism. Apart from that, this activity will overcome students' learning boredom and will develop students' psychology in learning